Sakada - Romero, Gloria; Koronel, Hilda; Rosal, Rosa; Bautista, Lualhati
This gripping drama tells about the impoverished lives of the Sakadas or sugarcane plantation workers under an exploitative feudal agricultural system, the imbalance between the poor peasants and the rich hacienderos in the distribution of wealth which triggered the passage of the Land Reform Act.